Characteristics of upper-extremity reactions to sudden lateral loss of balance in persons with stroke. (February 2021) - Handelzalts, Shirley; Steinberg-Henn, Flavia; Soroker, Nachum; Shani, Guy; Melzer, Itshak
Abstract: Background: Upper-extremity reactions are part of a whole-body response to counterweight the falling center of mass after unexpected balance loss. Impairments in upper-extremity reactions due to unilateral hemiparesis may contribute to stroke survivors propensity for falling. We aimed to characterize upper-extremity (paretic and non-paretic sides) reactive movements in response to lateral balance perturbations in Persons with Stroke vs. healthy controls. Methods: Twenty-six subacute persons with stroke and 15 healthy controls were exposed to multidirectional sudden unannounced surface translations in stance. Spatiotemporal parameters of upper- and lower-extremity balance responses to lateral perturbations were analyzed. Findings: In both groups reactive upper-extremity movement initiation preceded reactive step initiation. In response to a loss of balance toward the paretic side, persons with stroke demonstrated delayed movement initiation of both upper- and lower-extremity compared with healthy controls (In persons with stroke: 234.7 ± 60.0 msec and 227.1 ± 39.6 msec for upper extremities vs. 272.1 ± 59.1 msec for lower-extremity; and in controls: 180.1 ± 39.9 msec and 197.8 ± 61.3 msec for upper-extremities vs. 219.3 ± 40.8 msec for lower-extremity; p  = 0.001, Cohen's d's: 0.59–1.03) and a greater abduction excursion in the ipsilateral upper-extremity compared with the contralateral upper-extremity (In persons with stroke: 39.3 ± 23.6 cm vs. 24.9 ± 10.1 cm, respectively; In Controls: 42.6 ± 21.8 cm vs. 29.3 ± 17.3 cm, respectively). Interpretation: The faster upper-extremity reactive movement reactions compared to reactive step initiation in both persons with stroke and healthy controls suggests that balance recovery is an automatic "reflex-like" response. Delayed upper-extremity reactive reactions in conditions of surface translation toward the non-paretic side in persons with stroke may increase the risk of falls in the direction of the paretic side. Highlights: Persons with stroke demonstrated similar reactive response patterns to healthy persons. Persons with stroke demonstrated a delayed movement onset when balance is lost to the paretic side. Healthy people and persons with stroke have faster upper- vs. lower-limb movement initiation.